Overview of Second-Layer Screening Results in Identifying Cognitive Difficulties among Elementary School Students - Nindya Seva Kusmaningsih; Khoirun Annisah; Abdul Aziz; Abdul Khair (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2026)
This study aims to describe the results of the second-layer screening of students identified as having functional learning difficulties based on the PBS. The subjects were 59 students from grades 1–6 at SDN 1 Teros who were identified during the initial teacher-based screening. The research used a descriptive approach with data collection via a second-layer screening instrument focused on cognitive/intellectual functioning aspects. Data analysis was descriptive to illustrate the number and distribution of students at risk of cognitive difficulties. The results show that of the 59 students identified in the initial screening, 11 students were identified as being at risk for cognitive/intellectual difficulties after second-layer screening. These findings highlight the importance of multi-tiered screening in identifying students who may require further assessment due to potential cognitive difficulties in inclusive elementary schools.